2020
DOI: 10.1111/jce.14356
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary veins anatomical determinants of cooling kinetics during second‐generation cryoballoon ablation

Abstract: Aim The aim of the study was to investigate the role of anatomical characteristics of the pulmonary veins (PVs) determining cooling kinetics during second‐generation cryoballoon ablation (CbA). Methods and Results we enrolled all consecutive patients who underwent CbA for symptomatic atrial fibrillation in our center from January 2019 to March 2019. All patients had complete computed tomography scans of the heart before the ablation. Anatomical characteristics were tested for prediction of a nadir temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…It was defined as the distance between PV ostium and the first branch leaving the vein and was expressed in millimeter. Using these parameters, an anatomical performance score was evaluated for each vein as described earlier 14 . Briefly, the score was calculated by assigning one point for each of the following anatomical characteristics: PVd max ≤19.5 mm; PVd min ≤14.0; PV area ≤ 240 mm 2 ; PV trunk length ≤ 24.0 mm; and PV ovality ≥1.45.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was defined as the distance between PV ostium and the first branch leaving the vein and was expressed in millimeter. Using these parameters, an anatomical performance score was evaluated for each vein as described earlier 14 . Briefly, the score was calculated by assigning one point for each of the following anatomical characteristics: PVd max ≤19.5 mm; PVd min ≤14.0; PV area ≤ 240 mm 2 ; PV trunk length ≤ 24.0 mm; and PV ovality ≥1.45.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of the present study was to compare the biophysical parameters as well as complications and outcome to the established Arctic Front Advance Pro™ (AFAP, Medtronic) ablation system. Pulmonary vein (PV) anatomy can affect cooling kinetics and CB ablation outcome 14–17 . A recent study demonstrated an association between cross‐sectional orifice area of the superior PVs and outcome after CB ablation in patients with paroxysmal AF 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Borio et al confirmed that PV diameters, area of the ostium, ovality and trunk length were associated with temperatures achieved during CBA. They emphasize the cumulative role of these parameters (put together in a score) to predict satisfactory cryokinetics [34]. Some of these observations were confirmed in the study published by Chen et al, who reported an association between the lowest temperature achieved (T nadir ) and PV ostial diameter, but not shape [35].…”
Section: Discussionmentioning
confidence: 67%
“…Data on ostial area were extracted from 18 studies that matched the inclusion criteria (Borio et al, 2020; Choi et al, 2005; Chu et al, 2011; Clarke et al, 2021; Fodi et al, 2013; Hamdan et al, 2009; Hauser et al, 2015; Kajiyama et al, 2017; Kim et al, 2005; Krum et al, 2013; Lambert et al, 2018; Manghat et al, 2012; McLellan et al, 2014; Polaczek et al, 2019; Pontone et al, 2015; Rustogi et al, 2015; Shi et al, 2017; Tsao et al, 2005). The baseline characteristics of each analyzed study are collected in Table 6.…”
Section: Resultsmentioning
confidence: 99%